2013
DOI: 10.1021/jp400482v
|View full text |Cite
|
Sign up to set email alerts
|

pH Effects on Molecular Adsorption and Solvation of p-Nitrophenol at Silica/Aqueous Interfaces

Abstract: Resonance-enhanced second-harmonic generation (SHG) was used to examine the effects of solution pH and surface charge on para-nitrophenol (pNP) adsorption to silica/aqueous interfaces. During the early stages of monolayer formation, SHG spectra of interfacial pNP showed a single resonant excitation wavelength at approximately 313 nm regardless of solution pH. This resonance wavelength of adsorbed species is lower than the 318 nm excitation maximum of pNP in bulk aqueous solution. Experiments were performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…The presence of a high density of silanols even at higher pH is consistent with the observations of Walker and coworkers who observed binding of substituted phenols to an equal number of silanol and siloxides sites at pH 10.5. 30 Moreover, other studies that observed higher surface charge densities on colloidal silica than the value utilized here still result in only a fraction of sites being deprotonated at high pH based on a silanol density of 4.5/nm 2 (Table S3). 31 Of the deprotonatable sites, we find that pH history of the sample strongly influences their identity and relative distribution.…”
Section: ■ Results and Discussionmentioning
confidence: 57%
“…The presence of a high density of silanols even at higher pH is consistent with the observations of Walker and coworkers who observed binding of substituted phenols to an equal number of silanol and siloxides sites at pH 10.5. 30 Moreover, other studies that observed higher surface charge densities on colloidal silica than the value utilized here still result in only a fraction of sites being deprotonated at high pH based on a silanol density of 4.5/nm 2 (Table S3). 31 Of the deprotonatable sites, we find that pH history of the sample strongly influences their identity and relative distribution.…”
Section: ■ Results and Discussionmentioning
confidence: 57%
“…In molecular dynamics simulations of molecular adsorption at the solid-liquid interface, solute-solvent and substratesolvent interactions play an important role. 59,60 Therefore, special care should be taken in choosing a mutually compatible charge model for both solute and solvent. The YASARA software package with the Amber03 force field was chosen for the simulations because of its accuracy in modeling organic molecules in an aqueous environment.…”
Section: A Atomic Point Charge Model For Graphene Oxidementioning
confidence: 99%
“…2e), and has a p K a of 7.2. It can be exclusively neutral at acidic pH but dissociates to anionic form by increasing pH to basic conditions5051. This test would especially show us that which factor (size versus charge) is predominant in the size selective adsorption.…”
Section: Resultsmentioning
confidence: 96%